COVID-19 vaccine inequity in African low-income countries - Kunyenje, Chifundo Annessia; Chirwa, Gowokani Chijere; Mboma, Sebastian M.; Ng'ambi, Wingston; Mnjowe, Emmanuel; Nkhoma, Dominic; Ngwira, Lucky Gift; Chawani, Marlen Stacey; Chilima, Ben; Mitambo, Collins; Crampin, Amelia; Mfutso-Bengo, Joseph (Frontiers in Public Health, 2023)
Equitable access and utilization of the COVID-19 vaccine is the main exit strategy from the pandemic. This paper used proceedings from the Second Extraordinary Think-Tank conference, which was held by the Health Economics and Policy Unit (HEPU) at the Kamuzu University of Health Sciences (KUHES) in collaboration with the Malawi Ministry of Health (MoH), complemented by a review of literature. We found disparities in COVID-19 vaccine coverage among Low Income Countries (LICs). This is also the case among High Income Countries (HICs). The disparities are driven mainly by insufficient supply, inequitable distribution, limited production of the vaccine in LICs, weak health systems, and vaccine misconceptions. COVID-19 vaccine inequity continues to affect the entire world with the ongoing risks of emergence of new COVID-19 variants, increased morbidity and mortality and social and economic disruptions. In order to reduce the COVID-19 vaccination inequality in LICs, there is need to expand COVAX facility, waive intellectual property rights (IP), transform knowledge and technology acquired into vaccines, and conduct mass COVID-19 vaccination campaigns.